Phytonematode Problems associated with Some Economically Important Plants in Pishin District, Balochistan, Pakistan: Phytonematode Problems in Pishin District, Balochistan, Pakistan - Hussain, Faisal; Laghari, Saadullah Khan; Darban, Diam Ali; Farzana; Akbar, Muhammad (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2016)
Present study was conducted for nematodes communities associated with Pomegranate (Punica granatum L.), Grapes (Vitis vinifera L.), Peach (Prunus persica L.), Plums (Prunus domestica L.), Tobacco (Nicotiana tabacum L.), Apple (Malus pumila Mill.) and Apricot (Prunus armeniaca L.) at three localities of Pishin district, Balochistan province. In all investigated plant species twenty nematode species were recorded viz., Helicotylenchus digonicus, H. indicus, H. pseudorobustus, Hoplolaimus indicus, Meloidogyne incognita,M. javanica, Pratylenchus holdemani, P. penetrans, P. scribneri, P. thornei, Rotylenchus dalhousiensis, Scutylenchus rugosus, Tylenchorhynchus annulatus, T. curvus, T. trilineatus, Tylenchus filiformis, Xiphinema americanum, X. basiri, X. index and X. rivesi from the rhizosphere soil of above mentioned plant species. Among all species, Meloidogyne incognita and Xiphinema rivesi were dominant. The nematodes problem is rapidly increasing in Pakistan and widely damaging the host range by several species of phytonematodes. This investigation was designed to check the association, soil analysis, nematodes population density, incidence (%) and prevalence of nematodes associated with some crop and orchard plants of Pishin district, Balochistan.